Half-fluence Photodynamic Therapy for Central Serous Chorioretinopathy in a Patient Receiving Corticosteroids for Behçet’s Uveitis - Hüseyin Baran Özdemir; Nazgül Zhoroeva; Pınar Çakar Özdal; Şengül Özdek (Türk Oftalmoloji Dergisi, 2022)

(untitled)
Corticosteroid-induced central serous chorioretinopathy (CSCR) has been reported to develop in many intraocular inflammatory diseases and usually resolves spontaneously after discontinuation of corticosteroids. Patients without any improvement may require alternative therapies. In this case report, we present the case of a 35-year-old man with Behçet’s disease who had complaints of decreased vision due to CSCR in his left eye while using systemic corticosteroids along with cyclosporine and azathioprine. Half-fluence photodynamic therapy (PDT) was performed because the CSCR did not regress despite discontinuation of systemic corticosteroids. After treatment, his visual acuity increased with complete resolution of the subfoveal fluid. Half-fluence PDT seems to be an effective and safe treatment for patients who develop acute CSCR while under systemic or local corticosteroid therapy for intraocular inflammatory diseases such as Behçet’s uveitis and do not improve despite steroid discontinuation.